2016
DOI: 10.1534/g3.116.033829
|View full text |Cite
|
Sign up to set email alerts
|

Global Fitness Profiling Identifies Arsenic and Cadmium Tolerance Mechanisms in Fission Yeast

Abstract: Heavy metals and metalloids such as cadmium [Cd(II)] and arsenic [As(III)] are widespread environmental toxicants responsible for multiple adverse health effects in humans. However, the molecular mechanisms underlying metal-induced cytotoxicity and carcinogenesis, as well as the detoxification and tolerance pathways, are incompletely understood. Here, we use global fitness profiling by barcode sequencing to quantitatively survey the Schizosaccharomyces pombe haploid deletome for genes that confer tolerance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 109 publications
2
24
0
Order By: Relevance
“…Parallel mutant phenotyping by barcode sequencing (Bar-seq) [ 26 , 27 ] was used to identify haploid deletion mutants that are sensitive to 10 μM potassium dichromate (K 2 Cr 2 O 7 ), which slightly inhibits the growth of wild type (described in Materials and Methods). Growth inhibition (GI) scores were obtained for 2,887 mutants, leading to the identification of 68 genes required for chromate resistance ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parallel mutant phenotyping by barcode sequencing (Bar-seq) [ 26 , 27 ] was used to identify haploid deletion mutants that are sensitive to 10 μM potassium dichromate (K 2 Cr 2 O 7 ), which slightly inhibits the growth of wild type (described in Materials and Methods). Growth inhibition (GI) scores were obtained for 2,887 mutants, leading to the identification of 68 genes required for chromate resistance ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity to DNA damaging agents, such as camptothecin (CPT), hydroxyurea (HU), ionizing radiation (IR), and ultraviolet (UV) light, were amongst the most highly enriched phenotypes annotated to these genes ( Table 2 ). Indeed, hierarchical cluster analysis revealed that the chromium profile more closely resembles DNA damaging agents (CPT, HU and UV) than the toxic metal cadmium or metalloid arsenic ( Fig 1 ) [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we could speculate that, by up-regulating ISC biosynthesis, yeast cells expressing the two PLAC8 proteins may increase their survival because they provide essential cofactors to enzymes involved in DNA damage repair, thus reducing the high DNA mutation rate observed in cadmium-exposed yeast cells (Table 1). MM19, a late-acting CIA component likely implicated in the delivery of ISC into nuclear and cytosolic apoproteins [56], was found to be necessary to Schizosaccharomyces pombe to grow on cadmium [60].…”
Section: Resultsmentioning
confidence: 99%
“…The mapping resolution of QTL-seq can be high if phenotyping is not a bottleneck and a large number of plants can be bulked, as in the study by Rishmawi et al (102), which led to the direct identification of a candidate gene for a major root hair branching locus. Although the number of individuals per bulk is important for QTL resolution, it is noteworthy that the power of BSA also depends on the sequencing depth and the heritability of the trait studied (23,37,73,111). It is possible to dissect traits in populations with a more complex genetic architecture and to identify major and minor QTLs using this approach, as illustrated by a study of cold tolerance in rice (138) and a study of germination speed in Arabidopsis (143).…”
Section: Classical Quantitative Genetics Is Still Improvingmentioning
confidence: 99%